2004
DOI: 10.1007/s00330-004-2520-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal complications of bariatric Roux-en-Y gastric bypass surgery

Abstract: Obesity is rapidly becoming the most important public health issue in USA and Europe. Roux-en-Y gastric bypass is now established as the gold standard for treating intractable morbid or super obesity. We reviewed the imaging findings following this surgery in 234 patients. In this pictorial essay we present the CT and upper gastrointestinal contrast study appearances of the expected postoperative anatomy as well as a range of abdominal complications. The complications are classified into leaks, fistula and obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
1
20
2
Order By: Relevance
“…Ulcers may be caused by exposure to gastric acids from the gastrojejunal anastomosis or by ischemia. Studies in the literature report ulcers occurrence in 1% to 5% of cases, however, no case of ulcer was found in the present study (14)(15)(16)(17) . The present study has found one case of bezoar (2.4%), while the literature reports a 1.9% incidence (19) .…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Ulcers may be caused by exposure to gastric acids from the gastrojejunal anastomosis or by ischemia. Studies in the literature report ulcers occurrence in 1% to 5% of cases, however, no case of ulcer was found in the present study (14)(15)(16)(17) . The present study has found one case of bezoar (2.4%), while the literature reports a 1.9% incidence (19) .…”
Section: Discussioncontrasting
confidence: 80%
“…Upper gastrointestinal series have shown alterations in 51.2% of patients, however, not all gastroesophageal reflux diseases and hiatal hernias should be considered as postoperative surgical complications, considering that a preoperative examination has not been performed. With the exclusion of these complications, the total of remaining complications would correspond to 14.3%, a little below the percentage reported in the literature (20-25%) (14) . In another study performed by Arasaki et al, who have also performed the surgeries in the present study, 23% of patients have presented postoperative gastroesophageal reflux disease when a standard-sized silicone ring was utilized, and only 8% with a little larger ring, therefore it may be concluded that the resulting lower esophageal sphincter function may be related to some cases of postoperative gastroesophageal reflux disease (6) (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 61%
“…The transition point always lies proximal to the jejunojejunostomy, being typically situated at the level of the mesocolic window, nicely appreciated in the sagittal plane (Fig. 4c) [2,3,7,10,20,21]. Some authors consider it the most common type of the four IH after LRYGBP [4,7,8,17,20,23], while in our series, it was the least frequent one, although the majority of our patients had a retrocolic Roux limb.…”
Section: Transmesocolic Herniamentioning
confidence: 63%
“…After reviewing these previous publications [2, 3, 5-7, 9-11, 20, 21], we divided our analysis into MDCT features indicating SBO and indicating IH for the distinction between the four types of internal hernias (Table 1). [3,7,11] [ 2, 3,7,10,20,21] Central middle abdomen (anterior wall) [7,11] [ 7] Right paraumbilical abdomen (anterolateral wall) [11] [ 21]…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation